2008
DOI: 10.3310/hta12090
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness of diabetes education models for Type 2 diabetes: a systematic review

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 2 publications
5
105
0
5
Order By: Relevance
“…First, the experience of the UKPDS study demonstrated that the natural trend of HbA1c was to be worsened at a rate around 0.2% per year over a 10-year cohort observation period [38]. Second, the relative decrease in HbA1c here are consistent with the results of other studies with a very similar design and method and for various quality improvement programs: most of the studies observed a rather significant reduction of the Hba1c level, comprised between a 0.4 and a 1.0 point percent reduction, and then an increase in the proportion of diabetes patients under glycemic control [36][37][38][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 79%
“…First, the experience of the UKPDS study demonstrated that the natural trend of HbA1c was to be worsened at a rate around 0.2% per year over a 10-year cohort observation period [38]. Second, the relative decrease in HbA1c here are consistent with the results of other studies with a very similar design and method and for various quality improvement programs: most of the studies observed a rather significant reduction of the Hba1c level, comprised between a 0.4 and a 1.0 point percent reduction, and then an increase in the proportion of diabetes patients under glycemic control [36][37][38][39][40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 79%
“…The benefit of structured diabetes education programs has been confirmed in systematic review (1) and meta-analysis (2). Although the explicit changes in glycemic control after structured education have been well established, limited evidence (3) has demonstrated the effect of structured education on diabetesrelated complications.…”
mentioning
confidence: 95%
“…Other studies report a higher effect in education that is compact with meetings closely grouped together [13]. One systematic review reported that education delivered by several educators may improve the effect of education [43], while another review found that only one educator tended to do better than having a group of educators in the educations [14].…”
Section: Interactive Learningmentioning
confidence: 99%